Preparation method of sulfur-rich vacancy ferronickel bimetallic sulfide for full water decomposition
By using a one-step hydrothermal method to grow sulfur-rich nickel-iron bimetallic sulfide on the foam nickel-skeleton, the problems of high cost of existing catalyst materials and complex synthesis processes are solved, and efficient and low-cost catalytic performance and stability are achieved.
Patent Information
- Application Number
- CN202310957486.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-01
- Publication Date
- 2025-02-14
AI Technical Summary
In the existing electrolytic hydrogen production technology, hydrogen evolution and oxygen evolution catalyst materials are costly and toxic, which limits their large-scale application. The traditional catalyst synthesis process is complex and has a large energy consumption.
A one-step hydrothermal method is used to grow sulfur-rich nickel-iron bimetallic sulfide on the foam nickel skeleton. By introducing suitable sulfur vacancies and doping iron elements, the electronic structure of active ions is regulated and catalytic activity and stability are improved.
High-efficiency and low-cost catalytic performance is achieved, simplifies the synthesis process, reduces energy consumption, and the material can be directly used in the electrodes, avoiding additional electrode preparation steps.
Smart Images

Figure CN119447331A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of novel catalyst preparation, and specifically relates to a method for preparing sulfur-rich vacancy nickel-iron bimetallic sulfide grown on nickel foam, providing a preparation method with simple process and low cost. Background Art
[0002] With the rapid development of modern industry, the environmental and resource shortage problems caused by the massive consumption of energy are becoming increasingly serious. Therefore, it is urgent to develop new green energy sources. Hydrogen, as one of the most promising energy sources, has received widespread attention. However, the green and environmentally friendly water electrolysis hydrogen production technology has not been applied on a large scale in industry due to the slow hydrogen and oxygen evolution kinetics. In addition, the hydrogen and oxygen evolution catalyst materials currently used in commercial applications are precious metal materials, such as Pt / C for hydrogen evolution reaction and IrO2 / RuO2 for oxygen evolution reaction. Their high cost and toxicity limit their large-scale application. Therefore, the research direction of designing bifunctional catalytic materials with high efficiency, low cost and high stability has received more and more attention.
[0003] Generally, transition metal sulfides have attracted a lot of research due to their low cost, high conductivity and good stability. And transition metal sulfides show good oxygen evolution reaction performance in alkaline electrolytes. However, studies have found that a single transition metal sulfide cannot meet the requirements of water electrolysis performance. Therefore, strategies such as heteroelement doping and heterostructure have been proposed to optimize the catalytic performance of transition metal sulfides. With the deepening of research, researchers tend to understand the mechanism of electrocatalytic water decomposition from the perspective of electronic structure and the adsorption energy of materials on reactive substances, and propose more systematic strategies to optimize catalysts. Studies have reported that the doping of heteroelements and the appropriate introduction of vacancies can regulate the electronic structure near the active center ions, thereby improving the adsorption energy of the catalyst. However, most studies tend to focus only on morphology regulation or heterogeneous interface direction, and the combination of multiple regulation strategies often leads to cumbersome synthesis processes, harsh preparation conditions, and high energy consumption. Therefore, the present invention provides a method for preparing sulfur-rich vacancy nickel-iron bimetallic sulfide with a simple process and high repeatability, which further improves the catalytic activity and stability of the material by regulating the electronic structure of the active center, avoids the cumbersome and harsh synthesis process, and is conducive to large-scale application. Summary of the invention
[0004] The purpose of the present invention is to propose a simple and effective optimization strategy to synthesize sulfur-rich vacancy nickel-iron bimetallic sulfide with high catalytic performance. The method has a simple process and low energy consumption. It not only generates special micro-nano structures at the same time, but also introduces suitable defects in the material to regulate the electronic structure of active ions, thereby improving the catalytic activity of the material. In addition, the bimetallic sulfide grows on a nickel foam skeleton and can be directly used as an electrode material, eliminating the need for an additional electrode preparation process, and has good application prospects.
[0005] The objective of the present invention is achieved through the following technical solutions:
[0006] A nickel-iron bimetallic sulfide grown on nickel foam, characterized in that the nickel-iron bimetallic sulfide has a sea urchin spherical morphology, is evenly distributed on the nickel foam skeleton, has a size of about 2-5 μm, and the diameter of the thin rods on the sea urchin spherical particles is about 500 nm. In addition, the material contains a large number of sulfur vacancies.
[0007] A method for preparing sulfur-vacancy-rich nickel-iron bimetallic sulfide of the present invention comprises the following steps:
[0008] (1) Measure a certain volume of deionized water and ethylene glycol and mix them in a beaker;
[0009] (2) Weighing ferric chloride hexahydrate, ammonium fluoride, thiourea and aqueous hydrogen peroxide solution and dissolving them in the solution obtained in step 1), and stirring at room temperature to obtain a mixed solution;
[0010] (3) cutting the nickel foam into suitable sizes, respectively cleaning it with acetone, dilute hydrochloric acid and alcohol ultrasonically for 30 min, and then drying it with a hair dryer to obtain the treated nickel foam;
[0011] (4) transferring the mixed solution obtained in step 2) to a polytetrafluoroethylene liner, and then immersing the nickel foam obtained in step 3) in the solution in the polytetrafluoroethylene liner. Finally, the liner is sealed in a stainless steel reactor shell, and the reactor is placed in a forced air drying oven for hydrothermal reaction;
[0012] (5) After the reactor is cooled to room temperature, the sample is repeatedly rinsed with deionized water and alcohol, and then dried in a drying oven to obtain a nickel-iron bimetallic sulfide material grown on nickel foam.
[0013] Preferably, in step 1), the purity of the ethylene glycol is such that the volume ratio of ethylene glycol to deionized water is 1:1 (15 mL:15 mL).
[0014] Preferably, in step 2), the purity of the ferric chloride hexahydrate is 0.04 mol / L, the purity of the ammonium fluoride is 0.36 mol / L, the purity of the thiourea is 0.16 mol / L, and the volume of the aqueous hydrogen peroxide solution is 0-150 μL.
[0015] Preferably, in step 2), the stirring time is 10 min.
[0016] Preferably, in step 3), the concentration of the dilute hydrochloric acid is 2 mol / L, and the area of the nickel foam is 2*3 cm 2 .
[0017] Preferably, in step 4), the hydrothermal reaction temperature is 200° C. and the reaction time is 12 h.
[0018] Preferably, in step 5), the drying temperature is 45°C.
[0019] The nickel-iron bimetallic sulfide grown on the nickel foam skeleton of the present invention can be used as anode and cathode materials to form a full water splitting fuel cell without the need for an additional electrode preparation process, and can be directly used as a water splitting fuel cell system in an alkaline environment. The system includes the nickel-iron sulfide grown on the nickel foam skeleton as the cathode and cathode working electrodes and a 1 mol / L KOH solution.
[0020] Compared with the prior art, the present invention has the following advantages: (1) The sulfur-vacancy-rich nickel-iron bimetallic sulfide grown on the nickel foam skeleton provided by the present invention has a sea urchin spherical micro-nanostructure, the size of which is about 2-5 μm, and the diameter of the rod-like morphology on the sea urchin sphere is about 500 nm, which is evenly distributed on the nickel foam skeleton. This structure not only enhances the specific surface area of the material to expose more active sites, but also makes it easier to fully contact with the electrolyte. Its rough surface is more conducive to the desorption of the generated gas, avoiding the occupation of the active sites. (2) The previous technologies for introducing sulfur vacancies into materials mostly use relatively complex processes such as multi-step sulfurization, annealing at different temperatures, plasma treatment, and additional reaction with strong oxidants, and most of them consume a lot of energy. The present invention adopts a one-step hydrothermal method, and by adding a certain amount of hydrogen peroxide solution to the reaction solution, suitable sulfur vacancies can be introduced into the material. Because the preparation process is simple, highly repeatable and low in cost, it has a good prospect for commercial application. (3) The iron element in the material exists in the form of doping with nickel sulfide to form nickel-iron bimetallic sulfide. The doping of iron element will regulate the electronic structure of nickel active ions, but due to the presence of trace amounts of doped iron, the regulation of the coordination environment of nickel ions is limited. However, the introduction of appropriate sulfur vacancies will further regulate the coordination environment of nickel active ions. Therefore, the present invention directly regulates the electronic structure of the active center through defects, which not only promotes the improvement of the conductivity of the material, but also exposes more active sites of the material to regulate the adsorption energy of the active substance. (4) The sulfur vacancy-rich nickel-iron bimetallic sulfide in the present invention grows directly on the nickel foam skeleton and can be directly used for catalytic electrodes without the need for an additional electrode preparation process to add a binder, thereby avoiding the occupation of the active substance by the binder. In addition, the material grown directly on the nickel foam avoids the defect that the powder material is easy to fall off when preparing the electrode, and has better stability. Therefore, the material can have good hydrogen evolution, oxygen evolution and complete water splitting catalytic performance in alkaline electrolyte, and has a good application prospect. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a low-magnification scanning electron microscope image of the sulfur-vacancy-rich nickel-iron bimetallic sulfide prepared in the present invention.
[0022] Figure 2 This is a high-magnification scanning electron microscope image of the sulfur-vacancy-rich nickel-iron bimetallic sulfide prepared in the present invention.
[0023] Figure 3 This is a high-magnification transmission electron microscope image of the sulfur-vacancy-rich nickel-iron bimetallic sulfide prepared by the present invention.
[0024] Figure 4 The XRD image of the sulfur-vacancy-rich nickel-iron bimetallic sulfide prepared by the present invention.
[0025] Figure 5The XPS full spectrum of sulfur-vacancy-rich nickel-iron bimetallic sulfide prepared by the present invention.
[0026] Figure 6 The XPS spectrum of the S element of the sulfur-vacancy-rich nickel-iron bimetallic sulfide prepared by the present invention.
[0027] Figure 7 The LSV diagram of the OER of the sulfur vacancy-rich nickel-iron bimetallic sulfide in 1M KOH electrolyte prepared by the present invention.
[0028] Figure 8 This is a graph showing the OER stability test results of the sulfur-vacancy-rich nickel-iron bimetallic sulfide prepared in the present invention in 1M KOH electrolyte.
[0029] Fig. 9 The LSV diagram of HER of the sulfur-vacancy-rich nickel-iron bimetallic sulfide in 1M KOH electrolyte is obtained for the present invention.
[0030] Fig.10 This is a graph showing the HER stability test results of the sulfur-vacancy-rich nickel-iron bimetallic sulfide prepared in the present invention in 1M KOH electrolyte.
[0031] Fig.11 The LSV diagram of the complete water decomposition of the sulfur vacancy-rich nickel-iron bimetallic sulfide prepared by the present invention in 1M KOH electrolyte.
[0032] Fig.12 This is a graph showing the long-term complete water splitting stability test results of the sulfur-vacancy-rich nickel-iron bimetallic sulfide prepared by the present invention in 1M KOH electrolyte. DETAILED DESCRIPTION
[0033] The present invention will be further described in detail below through specific implementation modes, but the protection scope of the present invention is not limited to the following examples.
[0034] Example 1
[0035] (1) Weigh 0.04 mol / L of ferric chloride hexahydrate, 0.36 mol / L of ammonium fluoride, and 0.16 mol / L of thiourea and dissolve them in 15 mL of deionized water and 15 mL of ethylene glycol. Then, use a pipette to draw 150 μL of hydrogen peroxide solution and drip it into the above solution. Stir at room temperature for 10 min to obtain a mixed solution.
[0036] (2) Pre-treat the nickel foam and cut it into 2*3cm 2 The nickel foam is placed in acetone, dilute hydrochloric acid and alcohol in turn, and ultrasonically cleaned for 30 minutes respectively. After cleaning, it is dried with a hair dryer to obtain the treated nickel foam. The concentration of the dilute hydrochloric acid is 2 mol / L.
[0037] (3) The mixed solution prepared in step 1 was transferred to a 50 mL polytetrafluoroethylene-lined reactor, and then the nickel foam treated in step 2 was immersed in the solution. Finally, the reactor was sealed and placed in a forced air drying oven, and kept at 200° C. for 12 h to carry out a hydrothermal reaction.
[0038] (4) After the reaction is completed and cooled to room temperature, the sample is taken out, rinsed repeatedly with deionized water and alcohol, and then dried in a forced air drying oven at 45° C. to obtain sulfur-rich vacancy nickel-iron bimetallic sulfide grown on a nickel foam skeleton, which is recorded as NiFeS-NF-150.
[0039] Figure 1 This is a low-magnification scanning electron microscope picture of the sulfur-vacancy-rich nickel-iron bimetallic sulfide prepared in the present invention, showing that the nickel-iron bimetallic sulfide grows uniformly on the surface of the nickel foam skeleton.
[0040] Figure 2 This is a high-magnification scanning electron microscope picture of the sulfur-rich vacancy nickel-iron bimetallic sulfide prepared in the present invention, which shows that the morphology of the nickel-iron bimetallic sulfide is sea urchin spherical, with a size of about 2-5 μm, and the diameter of the rod-like morphology on the sea urchin sphere is about 500 nm.
[0041] Figure 3 This is a high-resolution transmission electron microscope image of the sulfur-rich vacancy nickel-iron bimetallic sulfide prepared in the present invention, indicating that the material phase is Ni3S2, without other phase components, proving that iron exists in a doped form.
[0042] Figure 4 The XRD spectrum of the sulfur-rich vacancy nickel-iron bimetallic sulfide prepared in the present invention shows that the material is composed of Ni3S2 phase, matches the JCPDS standard card No. 85-0775, and has no other impurity peaks.
[0043] Figure 5 This is the full XPS spectrum of the sulfur-vacancy-rich nickel-iron bimetallic sulfide prepared in the present invention, indicating the presence of Ni, Fe and S elements in the material, and also proving the successful doping of Fe element.
[0044] Figure 6 The XPS spectrum of the S element in the sulfur-rich vacancy nickel-iron bimetallic sulfide prepared in the present invention indicates the existence of Ni-S bonds, Fe-S bonds and sulfur vacancies in the sulfur-rich vacancy nickel-iron bimetallic sulfide.
[0045] Figure 7 The LSV diagram of the OER of the sulfur-rich vacancy nickel-iron bimetallic sulfide prepared in the present invention in 1M KOH electrolyte is shown in FIG. 2 The overpotential of the current density is 246 mV, which reduces the energy consumption of the reaction process.
[0046] Figure 8 This is a graph showing the OER stability test results of the sulfur-vacancy-rich nickel-iron bimetallic sulfide prepared in the present invention in 1M KOH electrolyte. After the material was subjected to 3000 cycles of CV testing in an alkaline environment, the measured LSV curve had a high degree of overlap with the LSV curve before the CV test, and there was no significant performance degradation.
[0047] Fig. 9 The LSV diagram of HER of the sulfur-rich vacancy nickel-iron bimetallic sulfide prepared in the present invention in 1M KOH electrolyte is shown in FIG. 2 The overpotential of the current density is 124 mV, which reduces the energy consumption of the reaction process.
[0048] Fig.10 This is a graph showing the HER stability test results of the sulfur-vacancy-rich nickel-iron bimetallic sulfide prepared in the present invention in 1M KOH electrolyte. After the material was subjected to 3000 cycles of CV testing in an alkaline environment, the measured LSV curve had a high degree of overlap with the LSV curve before the CV test, and there was no significant performance degradation.
[0049] Fig.11 The LSV diagram of the sulfur-rich vacancy nickel-iron bimetallic sulfide prepared in the present invention in the complete decomposition of water in 1M KOH electrolyte. The sulfur-rich vacancy nickel-iron bimetallic sulfide material is 10mA / cm 2 The overpotential of the current density is 1.63V, which reduces the energy consumption of the reaction process.
[0050] Fig.12 The graph is a long-term stability test result of the sulfur-rich vacancy nickel-iron bimetallic sulfide prepared in the present invention in 1M KOH electrolyte, indicating that the material has a high stability at 10 mA / cm 2 It can run stably for 36 hours at a current density of , and has good stability.
[0051] Example 2
[0052] (1) 0.04 mol / L of ferric chloride hexahydrate, 0.36 mol / L of ammonium fluoride, and 0.16 mol / L of thiourea were dissolved in 15 mL of deionized water and 15 mL of ethylene glycol, and stirred at room temperature for 10 min to obtain a mixed solution.
[0053] (2) Pre-treat the nickel foam and cut it into 2*3cm 2 The nickel foam is placed in acetone, dilute hydrochloric acid and alcohol in turn, and ultrasonically cleaned for 30 minutes respectively. After cleaning, it is dried with a hair dryer to obtain the treated nickel foam. The concentration of the dilute hydrochloric acid is 2 mol / L.
[0054] (3) The mixed solution prepared in step 1 was transferred to a 50 mL polytetrafluoroethylene-lined reactor, and then the nickel foam treated in step 2 was immersed in the solution. Finally, the reactor was sealed and placed in a forced air drying oven, and kept at 200° C. for 12 h to carry out a hydrothermal reaction.
[0055] (4) After the reaction is completed and cooled to room temperature, the sample is taken out, rinsed repeatedly with deionized water and alcohol, and then dried in a forced air drying oven at 45° C. to obtain sulfur-rich vacancy nickel-iron bimetallic sulfide grown on a nickel foam skeleton, which is recorded as NiFeS-NF-0.
[0056] The morphology and structure were characterized by scanning electron microscopy, XRD and XPS tests. The results showed that the sample without the addition of hydrogen peroxide solution also formed the Ni3S2 phase, but failed to form the urchin spherical morphology, and no sulfur vacancies were detected. This proves that the addition of hydrogen peroxide solution plays a key role in the formation of special morphology and sulfur vacancies.
[0057] The nickel-iron bimetallic sulfide prepared in this embodiment was tested in 1M KOH electrolyte and its oxygen evolution overpotential was 266 mV and hydrogen evolution overpotential was 179 mV, which reduced the additional energy consumption to a certain extent.
[0058] Comparative Example 1
[0059] This comparative example provides a method for preparing a sulfur-rich vacancy nickel-iron bimetallic sulfide. In the preparation method, except that the amount of the added hydrogen peroxide solution is 50 μL, the rest is the same as that in Example 1, and a sulfur-rich vacancy nickel-iron bimetallic sulfide is obtained, which is recorded as NiFeS-NF-50.
[0060] Comparative Example 2
[0061] This comparative example provides a method for preparing a sulfur-rich vacancy nickel-iron bimetallic sulfide. In the preparation method, except that the amount of the added hydrogen peroxide solution is 100 μL, the rest is the same as Example 1, and a sulfur-rich vacancy nickel-iron bimetallic sulfide is obtained, which is recorded as NiFeS-NF-100.
[0062] Comparative Example 3
[0063] This comparative example provides a method for preparing a sulfur-rich vacancy nickel-iron bimetallic sulfide. In the preparation method, except that the amount of the added hydrogen peroxide solution is 200 μL, the rest is the same as that in Example 1, and a sulfur-rich vacancy nickel-iron bimetallic sulfide is obtained, which is recorded as NiFeS-NF-200.
[0064] The morphology of the materials was characterized by scanning electron microscopy. It was found that the samples in Comparative Examples 1-3 all formed a sea urchin spherical morphology, but the addition of a suitable hydrogen peroxide solution had a great influence on the formation of the morphology. Too little (Comparative Example 1) and too much (Comparative Example 3) hydrogen peroxide solution could not form a more regular and uniform morphology.
[0065] The electrochemical performance of the samples in Comparative Examples 1-3 tested in 1M KOH electrolyte was inferior to that of the sample in Example 1. (NiFeS-NF-50: oxygen evolution 266mV, hydrogen evolution 154mV; NiFeS-NF-100: oxygen evolution 263mV, hydrogen evolution 128mV; NiFeS-NF-200: oxygen evolution 263mV, hydrogen evolution 149mV.)
[0066] The above is a specific embodiment of the sulfur-rich vacancy nickel-iron bimetallic sulfide grown on the nickel foam skeleton proposed and disclosed by the present invention. Those skilled in the art can refer to the content of the present invention for reference and implementation. Although the preparation technology of the present invention has been described in detail through examples, it is obvious that those skilled in the art can make relevant technical changes without departing from the present invention and scope. It should be pointed out that all similar changes and substitutions fall within the protection scope and disclosure scope of the present invention.
Claims
1. A nickel-iron bimetallic sulfide grown on nickel foam, the material having the following characteristics: the nickel-iron bimetallic sulfide has a sea urchin spherical morphology, is evenly distributed on the nickel foam skeleton, has a size of about 2-5 μm, the diameter of the thin rods on the sea urchin spherical particles is about 500 nm, and the material contains a certain number of sulfur vacancies.
2. The method for preparing the sulfur vacancy-rich nickel-iron bimetallic sulfide grown on the nickel foam skeleton as claimed in claim 1, characterized in that: It includes the following steps: (1) Measure a certain volume of deionized water and ethylene glycol and mix them in a beaker; (2) Weighing ferric chloride hexahydrate, ammonium fluoride, thiourea and aqueous hydrogen peroxide solution and dissolving them in the solution obtained in step 1), and stirring at room temperature to obtain a mixed solution; (3) cutting the nickel foam into suitable sizes, respectively cleaning it with acetone, dilute hydrochloric acid and alcohol ultrasonically for 30 min, and then drying it with a hair dryer to obtain the treated nickel foam; (4) transferring the mixed solution obtained in step 2) to a polytetrafluoroethylene liner, and then immersing the nickel foam obtained in step 3) in the solution in the polytetrafluoroethylene liner. Finally, the liner is sealed in a stainless steel reactor shell, and the reactor is placed in a forced air drying oven for hydrothermal reaction; (5) After the reactor is cooled to room temperature, the sample is repeatedly rinsed with deionized water and alcohol, and then dried in a drying oven to obtain a nickel-iron bimetallic sulfide material grown on nickel foam.
3. The method according to claim 2, characterized in that: In step 1), the volume ratio of ethylene glycol to deionized water is 1:1 (15 mL: 15 mL).
4. The method according to claim 2, characterized in that: In step 2), the concentration of ferric chloride hexahydrate is 0.04 mol / L, the concentration of ammonium fluoride is 0.36 mol / L, the concentration of thiourea is 0.16 mol / L, and the volume of the added hydrogen peroxide aqueous solution is 50-200 μL.
5. The method according to claim 2, characterized in that: In step 2), the stirring time is 10 min.
6. The method according to claim 2, characterized in that: In step 3), the concentration of the dilute hydrochloric acid is 2 mol / L, and the area of the nickel foam is 2*3 cm 2 .
7. The method according to claim 2, characterized in that: In step 4), the hydrothermal reaction temperature is 200° C. and the reaction time is 12 h.
8. The method according to claim 2, characterized in that: In step 5), the drying temperature is 45°C.
9. The nickel-iron bimetallic sulfide grown on the nickel foam skeleton as claimed in claim 1, characterized in that: The material can be used as cathode and anode materials to form a full water splitting fuel cell.
10. The use according to claim 9, characterized in that: The nickel-iron bimetallic sulfide grows directly on the nickel foam skeleton and does not require an additional electrode preparation process. It can be directly used as a water electrolysis fuel cell system in an alkaline environment. The system consists of nickel-iron sulfide grown on the nickel foam skeleton as the anode and cathode working electrodes and a 1 mol / L KOH electrolyte.